A study of prevalence of lower genital tract infections in HIV positive females - a cross sectional study - Bamniya, Jaishree; Singh, Pooja; Deora, Anuradha; Markan, Mili; Shah, Himanshu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The aim and objectives of the study was to determine the prevalence of lower genital tract infection (LGTI) with Candida spp, Trichomonas vaginalis, Neisseria gonorrhoeae, Chlamydia trachomatis, and bacterial vaginosis among symptomatic and asymptomatic women HIV seropositive females and control group attending gynec clinic. Methods: This cross-sectional descriptive study stratified by reported symptoms of vaginal discharge was carried out at STD Clinic, Zenana Hospital with approval from Hospital Ethics Committee and informed written consent from patients. 50 HIV seropositive women and 50 control patients were included in the study. All the patients under study were subjected to Grams staining of the vaginal smear, Pap smear and Colposcopy. HPV DNA testing was done in all HIV positive patients in control group only patients showing dyskaryotic changes on cytology were subjected to colposcopy. All HIV seropositive women were subjected to additional tests of CD 4 and CD 8 cell counts. Results: Prevalence of lower genital tract infections was high in HIV positive women (36%) as compared to HIV negative group (24%). Prevalence was significantly higher in HIV positive patients with CD 4 cell count less than 200 per microlitre that is 77.77 % with P value (0.007) which is highly significant statistically. More prevalence of Herpes (38%) Candidiasis (28%), Trichomoniasis (28%), followed by HPV (22%) and Chlamydia (8%). In control group, bacterial vaginosis is most common with co-infection with trichomoniasis. Conclusions: In lower genital tract infections, vaginal eco-system is altered. It increases risk of infection by opportunistic pathogens when the host defences became impaired. HIV positive females showed more prevalence of Herpes (38%) Candidiasis (28%), Trichomoniasis (28%), followed by HPV (22%) and Chlamydia (8%). In control group patients with bacterial vaginosis was most common along with co-infection with trichomoniasis. HIV positive females have more dyskaryotic changes on colposcopy especially in patients with HPV positive. So HPV test should be mandatory in HIV patients to diagnose Carcinoma cervix at its initial stages.